Outcomes and risk stratification for late antibody‐mediated rejection in recipients of ABO‐incompatible kidney transplants: a retrospective study. (2nd June 2017) - Lonze, Bonnie E.; Bae, Sunjae; Kraus, Edward S.; Holechek, Mary J.; King, Karen E.; Alachkar, Nada; Naqvi, Fizza F.; Dagher, Nabil N.; Sharif, Adnan; Desai, Niraj M.; Segev, Dorry L.; Montgomery, Robert A.
Summary: The required intensity of monitoring for antibody‐mediated rejection (AMR) after of ABO‐incompatible (ABOi) kidney transplantation is not clearly formulized. We retrospectively evaluated a single‐center cohort of 115 ABO‐incompatible (ABOi) kidney transplant recipients, of which 32% were also HLA incompatible (ABOi/HLAi) with their donors. We used an adjusted negative binomial model to evaluate risk factors for late AMR. Using this model, we risk‐stratified patients into high‐ and low‐risk groups for the development of late AMR; 26% of patients had at least one AMR episode; 49% of AMR episodes occurred within 30‐days after transplant and were considered early AMR. Patients with an early AMR episode had a 5.5‐fold greater incidence of developing late AMR [IRR = 5.5, (95% CI: 1.5–19.3), P = 0.01]. ABOi/HLAi recipients trended toward increased late AMR risk [IRR = 1.9, (95% CI: 0.5–6.6), P = 0.3]. High‐risk recipients (those with an early AMR or those who were ABOi/HLAi) had a sixfold increased incidence of late AMR [IRR = 6.3, (95% CI: 1.6–24.6), P = 0.008] versus low‐risk recipients. The overall incidence of late AMR was 20.8% vs. 1.5% in low‐risk recipients. Changes in anti‐A/B titer did not correlate with late AMR (IRR = 0.9 per log titer increase, P = 0.7). This risk‐stratification scheme uses information available within 30 days of ABOi transplantation to determine risk for late AMR and can help direct longitudinal follow‐up for individual patients.